Investigation on the load-displacement curves of a human healthy heel pad: In vivo compression data compared to numerical results - Fontanella, C.G.; Matteoli, S.; Carniel, E.L.; Wilhjelm, J.E.; Virga, A.; Corvi, A.; Natali, A.N. (Medical engineering & physics, 2012)
The aims of the present work were to build a 3D subject-specific heel pad model based on the anatomy revealed by MR imaging of a subject's heel pad, and to compare the load–displacement responses obtained from this model with those obtained from a compression device used on the subject's heel pad. A 30 year-old European healthy female (mass=54kg, height=165cm) was enrolled in this study. Her left foot underwent both MRI and compression tests. A numerical model of the heel region was developed based on a 3D CAD solid model obtained by MR images. The calcaneal fat pad tissue was described with a visco-hyperelastic model, while a fiber-reinforced hyperelastic model was formulated for the skin. Numerical analyses were performed to interpret the mechanical response of heel tissues. Different loading conditions were assumed according to experimental tests. The heel tissues showed a non-linear visco-elastic behavior and the load–displacement curves followed a characteristic hysteresis form. The energy dissipation ratios measured by experimental tests (0.25±0.02 at low strain rate and 0.26±0.03 at high strain rate) were comparable with those evaluated by finite element analyses (0.23±0.01 at low strain rate and 0.25±0.01 at high strain rate). The validity and efficacy of the investigation performed was confirmed by the interpretation of the mechanical response of the heel tissues under different strain rates. The mean absolute percentage error between experimental data and model results was 0.39% at low strain rate and 0.28% at high strain rate.